The impact of frequently encountered cardiovascular risk factors on sexual dysfunction in rheumatic disorders. (8th May 2013) - Anyfanti, P.; Pyrpasopoulou, A.; Triantafyllou, A.; Doumas, M.; Gavriilaki, E.; Triantafyllou, G.; Gkaliagkousi, E.; Chatzimichailidou, S.; Petidis, K.; Avagianou, P.‐A.; Zamboulis, C.; Aslanidis, S.; et al.
Summary Traditional cardiovascular risk factors have been acknowledged as major contributors to sexual dysfunction in the general population. The purpose of this study was to explore their impact on sexual function in rheumatologic patients. A total of 557 consecutive rheumatologic patients, 449 females and 108 males, had their sexual function evaluated with the Female Sexual Functioning Index (FSFI) and the International Index of Erectile Function (IIEF) questionnaire respectively. Personal data regarding presence of cardiovascular risk factors were collected and analysed in association with the FSFI and IIEF scores. Mean age of the participants was 54.1 ± 14.1 years, mean body mass index was 27.5 ± 5.29 and mean systolic and diastolic blood pressure was 130.5 ± 19.82 and 79.5 ± 10.51 mmHg respectively. Hypertension was present in 39% of the participants, diabetes mellitus in 10.2%, dyslipidaemia in 33.6% and history of cardiovascular events in 8.6%, whereas smoking was recorded by 28.4% and alcohol consumption by 7.4%. Sexual dysfunction affected 68.6% of our study population (73.5% of females and 48.1% of males, p < 0.001). Logistic regression analysis revealed that age was the only factor associated with a significantly higher prevalence of sexual dysfunction (p < 0.001 for both genders, p = 0.013 in males and p < 0.001 in females). Increased age was identified as the only independent predictor of sexual dysfunction in our population. Apart from age, traditional cardiovascular risk factors failed to explain the increased prevalence of sexual dysfunction in these patients. Other contributing factors (physical and/or psychological) might account for the increased occurrence of sexual dysfunction in rheumatic disorders.